Lessons from a fatigue prediction challenge for an aircraft wing shear tie post. (June 2019) - Main, B.; Evans, R.; Walker, K.; Yu, X.; Molent, L.
Highlights: Presents significant outcomes of a fatigue test program under a complex spectrum. Present blind predictions using a variety of fatigue prediction tools. A geometry factor was derived from experimental data. Abstract: Like many aircraft operators and maintainers, the Royal Australia Air Force requires the most robust of metal fatigue analysis tools for both informed acquisition and cost effective sustainment of aircraft. The Defence Science and Technology Group has been investigating and enhancing metal fatigue predictive tools for many years. This paper describes a local blind-prediction challenge for a series of coupons manufactured from Aluminium Alloy 7050-T7451 plate simulating a combat aircraft wing root shear restraint (or shear tie post) subject to a combined aerodynamic buffet and manoeuvre load spectrum. Analysts were provided with details including the geometry, material and loading, and were asked to predict the total fatigue life. Results from a detailed three dimensional finite element model of a cracked or uncracked test coupon were also available to the analysts. The results from two separate, independent blind predictions are presented and assessed along with further non-blind analyses to evaluate the current capabilities. The exercise found that accurate and reliable predictions are possible in a case like this, but the results are dependent on the availability of high-fidelity short crack rate data and a suitable stress intensity Beta solution. The work will provide confidence in existing fatigue life modelling capabilities leading to improvements in safety, availability and cost reduction.